2021
DOI: 10.1016/j.heliyon.2021.e07828
|View full text |Cite
|
Sign up to set email alerts
|

Prednisone prevents particle induced bone loss in the calvaria mouse model

Abstract: Introduction Glucocorticoids are essential in the treatment of many chronic inflammatory and malignant diseases but are known to have detrimental effects on bone. This study aimed to investigate the effects of prednisone on osteoclast functioning in vivo in the calvaria particle-induced bone loss mouse model. Methods 12-week-old male C57BL6/J mice received subcutaneously implanted prednisone (2.5 mg/d, 60 day release (n = 14)) or placebo pelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…This study used FVB mice, which are the most susceptible strain to study GC-induced osteonecrosis, but at 13-weeks of age, they may be less sensitive to the catabolic action of GC on trabecular bone. Indeed, the effects of GC are age-dependent, such that others have shown that GC’s effect on trabecular bone is unchanged ( 70 , 72 , 75 , 76 ) or elevated ( 75 ) in younger mice. Another variable to consider is GC dosing effects, as shorter exposure to higher dose GC ( 77 ) or prolonged lower dose GC ( 40 ) treatment in younger mice can cause bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…This study used FVB mice, which are the most susceptible strain to study GC-induced osteonecrosis, but at 13-weeks of age, they may be less sensitive to the catabolic action of GC on trabecular bone. Indeed, the effects of GC are age-dependent, such that others have shown that GC’s effect on trabecular bone is unchanged ( 70 , 72 , 75 , 76 ) or elevated ( 75 ) in younger mice. Another variable to consider is GC dosing effects, as shorter exposure to higher dose GC ( 77 ) or prolonged lower dose GC ( 40 ) treatment in younger mice can cause bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent investigation, a novel Keap-1 inhibitor, iKeap1, was shown to protect osteoblast from chemically generated oxidative assault and apoptosis by improving Nrf2-mediated expression of cytoprotective factors [ 123 ]. Treatment with a low dose of glucocorticoids, including dexamethasone (DEX), cortisone, and prednisolone, over a short time was shown to regulate bone remodeling and maintain homeostasis of the bone tissues [ 124 ]. However, administering the same drugs at a higher dosage over a long time elicited OP [ 125 ] and osteonecrosis via upregulation of glycogen synthase kinase-3β (GSK3β) gene expression and its enzyme activity [ 126 ].…”
Section: Cellular and Molecular Mechanisms Of Bone Health-promoting P...mentioning
confidence: 99%